Workplace harassment from the victim's perspective: A theoretical model and meta-analysis. - Bowling, Nathan A.; Beehr, Terry A. (Journal of Applied Psychology, 2006)
Although workplace harassment affects the lives of many employees, until recently it has been relatively ignored in the organizational psychology literature. First, the authors introduced an attribution- and reciprocity-based model that explains the link between harassment and its potential causes and consequences. The authors then conducted a meta-analysis to examine the potential antecedents and consequences of workplace harassment. As shown by the meta-analysis, both environmental and individual difference factors potentially contributed to harassment and harassment was negatively related to the well-being of both individual employees and their employing organizations. Furthermore, harassment contributed to the variance in many outcomes, even after controlling for 2 of the most commonly studied occupational stressors, role ambiguity and role conflict.